Heterodox Economics Approach to Business Co-operation - Braga, Vitor (Journal of Entrepreneurship, Business and Economics; Vol 1 No 1/2 (2013), 2013)
Purpose- Economics and business have evolved as sciences in order to accommodate more of ‘real world’ solutions for the problems approached. In many cases, both business and economics have been supported by other disciplines in order to obtain a more complete framework for the study of complex issues. The aim of this paper is to explore the contribution of three heterodox economics disciplines to the knowledge of business co-operation. Design/methodology/approach- This approach is theoretical and it shows that many relevant aspects of business co-operation have been proposed by economic geography, institutional economics, and economic sociology. Findings- This paper highlights the business mechanisms of co-operation, reflecting on the role of places, institution and the social context where businesses operate. Research Implications- It contributes with a theoretical framework for the explanation of business co-operations and networks that goes beyond the traditional economics theories. Originality/value- This paper contributes with a framework for the study of business co-operation both from an economics and management perspective. This framework embodies a number of non-quantitative issues that are critical for understanding the complex networks in which firms operate. Conceptual paper Reference to this paper should be made as follows: Braga, V (2013). “Heterodox Economics Ap-proach to Business Co-operation”, Journal of Entrepreneurship, Business and Economics, Vol. 1 No. 1/2, pp. 72–81.